1995
DOI: 10.1126/science.7886455
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Protein G o in Multiple Aspects of Behavior in C. elegans

Abstract: The goa-1 gene encoding the alpha subunit of the heterotrimeric guanosine triphosphate-binding protein (G protein) Go from Caenorhabditis elegans is expressed in most neurons, and in the muscles involved in egg laying and male mating. Reduction-of-function mutations in goa-1 caused a variety of behavioral defects including hyperactive movement, premature egg laying, and male impotence. Expression of the activated Go alpha subunit (G alpha o) in transgenic nematodes resulted in lethargic movement, delayed egg l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
241
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(249 citation statements)
references
References 34 publications
(8 reference statements)
8
241
0
Order By: Relevance
“…As in mammals, GOA-1 G o ␣ is ubiquitously expressed in the nervous system in C. elegans and reported to be involved in many aspects of behavior (21,22). In our study, we demonstrated that GOA-1 modulates sensory responses, specifically, olfactory adaptation (and salt chemotaxis plasticity) in C. elegans.…”
Section: Down-regulation Of Gq␣-dag Signaling By Go␣ Is Crucial For Omentioning
confidence: 55%
See 1 more Smart Citation
“…As in mammals, GOA-1 G o ␣ is ubiquitously expressed in the nervous system in C. elegans and reported to be involved in many aspects of behavior (21,22). In our study, we demonstrated that GOA-1 modulates sensory responses, specifically, olfactory adaptation (and salt chemotaxis plasticity) in C. elegans.…”
Section: Down-regulation Of Gq␣-dag Signaling By Go␣ Is Crucial For Omentioning
confidence: 55%
“…However, the mode of action of G o in these behaviors is unclear. C. elegans has 21 G protein ␣-subunit genes (19,20), and the only orthologue of mammalian G o ␣ is encoded by the goa-1 gene (21,22). Mutations in goa-1 cause various defects in behaviors, including locomotion and egg laying.…”
mentioning
confidence: 99%
“…One possible explanation for the observed specificity of heterotrimer subunit composition is a compartmentalization of the signal transduction elements in the plasma membrane of intact cells [26]. Nevertheless, the G~o subunit is currently without a specific effector-regulating function, though results obtained from modulating gene expression of the G~o gene in the roundworm Caenorhabditis elegans underline an important role of this G protein in various neuronal functions [51,52].…”
Section: Functions Of G Proteins On Organelle Membranesmentioning
confidence: 99%
“…In particular, G protein-mediated signaling pathways such as Go-or Gqmediated pathways have been well characterized in C. elegans (19,20). In addition, analysis of G␣12 expression in C. elegans (21) and its signaling via tpa-1, a homologue of protein kinase C in pharyngeal muscle cells, have recently been reported (22).…”
mentioning
confidence: 99%